Kalium Aluminium Sulfat (Tawas) vs Deodoran Konvensional dalam Mengatasi Bau Badan pada Remaja: Studi Observasional Potong Lintang - Juliani, Vitri; Baruri, Rohan Eza (MAN Insan Cendekia Siak, 2025)
Body odor in adolescents is a common issue caused by bacterial decomposition of sweat compounds, particularly affecting teenagers due to hormonal changes and increased sebaceous gland activity. Natural mineral deodorants containing alum (potassium aluminum sulfate) have gained attention as safer alternatives to conventional antiperspirants. To evaluate and compare the effectiveness of alum stone versus conventional deodorants in managing body odor among adolescent students in boarding school environments through observational analysis. An observational cross-sectional study was conducted among 120 students aged 16-18 years at MAN Insan Cendekia Siak boarding school over 8 weeks. Participants were divided into two groups based on their existing deodorant use: alum stone users (n=60) and conventional deodorant users (n=60). Body odor assessment was performed using validated sensory evaluation and bacterial culture analysis. Data were collected through structured observations and questionnaires. The alum user group demonstrated significant reduction in body odor intensity scores and showed bacterial count reduction of 78.3% compared to baseline measurements. User satisfaction rate reached 85.2% with minimal reported adverse effects. Long-term effectiveness was maintained throughout the observation period with consistent results. Observational analysis demonstrates that alum stone shows promising effectiveness in managing body odor among adolescents, providing a natural alternative for daily personal hygiene in boarding school environments. Further controlled studies are recommended to establish definitive efficacy.